The Characterization of Recycled Concrete Aggregate (RCA) as Vertical Filter For Removing Phosphorus - Adnan, Suraya Hani; A Roni, Norwardatun; Hamidon, Nuramidah; Tuan Ismail, Tuan Noor Hasanah (Penerbit UTHM, 2020)
A crush concrete aggregate is one of the alternative treatments for the removal of phosphorus. It is a low-cost, alternative technology for removing nutrients from wastewater. Some of the advantages of crush concrete are its cost efficiency, high availability and relatively easy installation compared to conventional methods. According to previous studies, one of the alternative filter media for the removal of phosphorus is recycled concrete aggregate (RCA). RCA has a high capability for removing phosphorus. It is also easily available and incurs a low cost. Besides, it is a sustainable method since RCA is a recycled product from the construction site.